CORONARY HEART DISEASE PATIENTS' LEARNING NEEDS - Aan Nuraeni; Ristina Mirwanti; Anastasia Anna (Belitung Nursing Journal, 2018)
Background: Patients with coronary heart disease (CHD) should have good self-management capabilities. This is determined by the effective of health education which is based on the assessment of patients’ learning needs and consideration of health personnel. On the other hand, the study of perceptions of CHD patients’ learning needs in Indonesia is little known. Objective: This study aimed to identify the CHD patients’ learning needs. Methods: This study was a descriptive quantitative with cross-sectional approach. Population was CHD patients in one of the referral hospitals in West Java Indonesia. Samples were recruited using consecutive sampling technique for a 2-month period (n=106). Data were collected using TR-CPLNI instrument and analyzed using descriptive quantitative and Kruskal Wallis test. Results: The order of learning needs based on the highest to the lowest mean was anatomy and physiology of heart (4.42); medication information (4.33); cardiopulmonary information (4.32); life style (4.28); dietary information (4.19); symptom management (4.08); psychology (4.07); and physical activity (3.64). The significant differences (p<0.05) based on ward categories were learning needs of dietary information (p=0.002); physical activity (p=0.009) and symptom management (p=0.037), with the highest needs respectively were in High Care Unit (HCU); HCU; and non-intensive care unit. Conclusions: These eight learning needs were important for CHD patients. However, the priority of the patients’ learning needs were seen by category of ward or recovery phase and illness duration different from each other. Therefore, this can be a consideration in providing education to CHD patients.